2018
DOI: 10.1088/1361-6528/aac483
|View full text |Cite
|
Sign up to set email alerts
|

High speed chalcogenide glass electrochemical metallization cells with various active metals

Abstract: We fabricated electrochemical metallization cells using a GaLaSO solid electrolyte, an InSnO inactive electrode and active electrodes consisting of various metals (Cu, Ag, Fe, Cu, Mo, Al). Devices with Ag and Cu active metals showed consistent and repeatable resistive switching behaviour, and had a retention of 3 and >43 days, respectively; both had switching speeds of <5 ns. Devices with Cr and Fe active metals displayed incomplete or intermittent resistive switching, and devices with Mo and Al active electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The dominant RS mechanisms in chalcogenide-based RS devices are the phase change mechanism [92,95,182,185] and ECM [92,176,186,187]. The increase in ionic conductivity associated with the phase transition with respect to temper ature is a typical phenomenon found in chalcogenide materials such as silver selenide (Ag 2 Se), copper(I) selenide (Cu 2 Se) and Ag 2 S [92,182,185].…”
Section: Chalcogenidesmentioning
confidence: 99%
“…The dominant RS mechanisms in chalcogenide-based RS devices are the phase change mechanism [92,95,182,185] and ECM [92,176,186,187]. The increase in ionic conductivity associated with the phase transition with respect to temper ature is a typical phenomenon found in chalcogenide materials such as silver selenide (Ag 2 Se), copper(I) selenide (Cu 2 Se) and Ag 2 S [92,182,185].…”
Section: Chalcogenidesmentioning
confidence: 99%
“…The absence of resistive switching for Cr-CrO x /GST/Pt in contrast to Cr/GST/Pt underlines the critical role of an oxidefree interface. Indeed, for the oxide-containing Cr/GaLaSO/ ITO reported by Hughes et al [47] only incomplete resistive switching and fast passivation was found. From the current Although for Au/GST/Pt no signs of resistive switching were observed, it should be noted that filament formation based on Au was reported for Au/SiO 2 /Pt [28].…”
Section: Ecm Cells Without Switchingmentioning
confidence: 93%
“…Abrupt set processes have been widely reported in conventional ECM memristors with different metal ions and non-ferroelectric electrolytes [41][42][43][44] . We presume that the gradual set switching behavior observed in Cu and Ni/ PZT/LSMO is induced by the correlation between polarization bound charges and metal ions.…”
Section: Rs Behaviors Of Different Metal/pzt/lsmo Structuresmentioning
confidence: 99%